Inhibition of soluble epoxide hydrolase does not improve the course of congestive heart failure and the development of renal dysfunction in rats with volume overload induced by aorto-caval fistula - Červenka, L; Melenovský, V; Husková, Z; Sporková, A; Bürgelová, M; Škaroupková, P; Hwang, S H; Hammock, B D; Imig, J D; Sadowski, J (Physiological research, 2015)
The detailed mechanisms determining the course of congestive heart failure (CHF) and associated renal dysfunction remain unclear. In a volume overload model of CHF induced by creation of aorto-caval fistula (ACF) in Hannover Sprague-Dawley (HanSD) rats we explored the putative pathogenetic contribution of epoxyeicosatrienoic acids (EETs), active products of CYP-450 dependent epoxygenase pathway of arachidonic acid metabolism, and compared it with the role of the renin-angiotensin system (RAS). Chronic treatment with cis-4-[4-(3-adamantan-1-yl-ureido) cyclohexyloxy]benzoic acid (c-AUCB, 3 mg/l in drinking water), an inhibitor of soluble epoxide hydrolase (sEH) which normally degrades EETs, increased intrarenal and myocardial EETs to levels observed in sham-operated HanSD rats, but did not improve the survival or renal function impairment. In contrast, chronic angiotensin-converting enzyme inhibition (ACEi, trandolapril, 6 mg/l in drinking water) increased renal blood flow, fractional sodium excretion and markedly improved survival, without affecting left ventricular structure and performance. Hence, renal dysfunction rather than cardiac remodeling determines long-term mortality in advanced stage of CHF due to volume overload. Strong protective actions of ACEi were associated with suppression of the vasoconstrictor/sodium retaining axis and activation of vasodilatory/natriuretic axis of the renin-angiotensin system in the circulating blood and kidney tissue.
Keywords: náhodné rozdělení; renální insuficience; Angiotensin I; Angiotensin-Converting Enzyme Inhibitors; Drug Evaluation, Preclinical; preklinické hodnocení léčiv; 8,11,14-Eicosatrienoic Acid; Heart Failure; srdeční selhání; epoxidové sloučeniny; Urea; ledviny; Angiotensin II; kyselina 8,11,14-eikosatrienová; angiotensin II; inhibitory ACE; Kidney; Ultrasonography; krysa rodu Rattus; Epoxide Hydrolases; zvířata; Peptide Fragments; močovina; ultrasonografie; Renal Insufficiency; Male; epoxid hydrolasy; benzoáty; peptidové fragmenty; Rats; myokard; Animals; Epoxy Compounds; Myocardium; mužské pohlaví; Renin-Angiotensin System; Disease Models, Animal; Random Allocation; renin-angiotensin systém; Benzoates; angiotensin I; modely nemocí na zvířatech